Changes in Students’ Writing Style After Using a Grammar Checking App: A Reflective Qualitative Study - Asla Alayya; Nur Indah Ramadhani; Salsabila Lubis; Nikmatul Wahidah; Muhammad Hasyimsyah (English Education Study Program FKIP Universitas Alwashliyah Medan, 2026)
Students' writing growth has been greatly impacted by the incorporation of grammar-checking software into language learning, especially in English as a Foreign Language (EFL) contexts. This study focuses on the linguistic and cognitive aspects of writing in order to examine how students' writing styles alter after utilizing a grammar-checking program. 25 undergraduate students taking an academic writing course participated in this study, which used a qualitative reflective design. Semi-structured interviews, reflective diaries, pre- and post-writing assignments, and document analysis were used to gather data. To find patterns of change in grammatical accuracy, lexical diversity, sentence complexity, coherence, and writing autonomy, the data were subjected to thematic analysis. The results show that using grammar checking software greatly enhances students' writing, especially in terms of improving grammatical accuracy, increasing vocabulary, and encouraging more intricate sentence patterns. Students also exhibit higher levels of engagement with the editing process and metacognitive awareness. However, the study also highlights some disadvantages, like an excessive dependence on automated feedback and a poor critical comprehension of grammatical principles. Grammar checking software is therefore a useful tool for enhancing writing quality, but in order to guarantee deeper learning and critical engagement, its use should be accompanied by instructional assistance.